HUBUNGAN ADEKUASI HEMODIALISIS DENGAN TEKANAN DARAH PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Dicha Fitra Rafinda (FKU 16 UMY 017, 2016)
Background: Chronic Kidney Disease (CKD) is a pathophysiological process with variative etiologies that can decreasing renal function progresively. It can be marked with Glomerulus Filtration Rate (GFR) decrease and creatinin level increase. Hemodialysis (HD) is one of the important method in acute or chronic renal disease treatment to maintain homeostasis of the body, that also is the goal of HD itself. Hypertension is a clinical symptoms that usually appear in CKD patients undergoing HD (prevalence 70-80%). Stable blood pressure can prevent and decrease risk of cerebro-cardiovascular diease. Objective: To find out the relationship between hemodialysis adequacy and blood pressure in CKD patients undergoing HD in PKU Muhammadiyah Yogyakarta Hospital. Methods: This study was an observational analytical with cross-sectional approach of which results are presented in descriptive followed by comparison analysis using Independent sample-t test and correlative analysis using Pearson test to determine the relationship between two variables. The subjects were CKD patients undergoing HD in PKU Muhammadiyah Yogyakarta Hospital. The research instruments were a digital tensimeter that usually used in PKU Muhammadiyah Yogyakarta Hospital. Results and Discussion: The number of male respondents were 22 (59,3%), and the female respondents were 32 patients (40,7%). The mean of systolic and diastolic before and after HD between male and female respondents whose adequate or inadequate hemodialysis were significantly unidentic. Twenty-six respondents (48,1%) have adequate HD and 28 respondents (51,9%) have inadequate HD. Conclusion: There are no significance relationship between HD adequacy with the mean of systolic (p=0,160) and diastolic (p=0,313) blood pressure in patientsmaintenance HD two times per week, nor the mean of systolic (p=0,492) and diastolic (p=0,211) in patients maintenance HD three times per week